Highly effective removal of nickel ions from wastewater by calcium-iron layered double hydroxide - Li, Ning; Yuan, Mingjie; Lu, Sheng; Xiong, Xiaoli; Xie, Zhigang; Liu, Yongsheng; Guan, Wei (Frontiers in Chemistry, 2023)
Water pollution due to heavy metals has become a universal environmental problem. Ni(II) is a common heavy metal ion in polluted wastewater, which has high toxicity and carcinogenicity. In this study, the structure of a calcium-iron layered double hydroxide (Ca-Fe-LDHs) was synthesized and characterized by FTIR, XRD, SEM and XPS. Then, Ni(II) ion was effectively removed by Ca-Fe-LDHs and its mechanism for this materials was described. The maximum adsorption capacity of Ni(II) for Ca-Fe-LDHs was 418.9 mg‧g−1 when the initial concentration of Ni(II) was 1 g/L. The adsorption and removal of Ni(II) by Ca-Fe-LDHs was attributed to the action of hydroxyl groups on the hydrotalcite, generating surface capture. Ni(OH)2)0.75(H2O)0.16(NiCO3)0.09, Ni(OH)2, NiO, NiSO4 and other precipitates were generated on its surface. And a small amount of Ni-Fe-LDHs was generated through isomorphic transition before hydrolysis. Therefore, surface capture and isomorphic transition enhanced the removal efficiency of Ni(II) with Ca-Fe-LDHs, making Ca-Fe-LDHs as a potential material for effective removal of Ni(II).